Validity and Reliability of a Non-invasive Test to Assess Quadriceps and Hamstrings Strength in Athletes - Mondin, Davide; Owen, Julian A.; Negro, Massimo; D’Antona, Giuseppe (Frontiers in Physiology, 2018)
Modifiable risk factors for hamstring injury include lack of strength, fatigue and muscle strength asymmetry. Assessing lower body strength in the field is problematic as “gold standard assessment” are expensive, non-portable and assessment is time-consuming. Therefore, the objective of this study was to examine the validity and reliability of an adapted aneroid sphygmomanometer test of hamstring and quadricep strength. In 14 active males (age 23.1 ± 2.5 years; height 180.9 ± 8.2 cm; weight 88.4 ± 8.5 kg). concurrent validity was assessed by comparing the adapted sphygmomanometer assessment at 30 and 90° of knee flexion to isokinetic dynamometry using Pearson product-moment correlation. The reliability of the adapted sphygmomanometer was assessed in 10 professional rugby players (age 21.5 ± 2.6 years; height 177.2 ± 5.8 cm; weight 92.7 ± 5.8 kg ) across two visits. Sphygmomanometer strength assessments of hamstring and quadriceps were associated with isokinetic measures (Quadricep: right, r = 0.386, 95% CI = 0.136–0.866, p < 0.05; left, r = 0.431, 95% CI = 0.193–0.880, p < 0.05), hamstring strength at 90° of knee flexion (Hamstring: right, r = 0.545, 95% CI = 0.342–0.912, p < 0.01; left, r = 0.643, 95% CI = 0.473–0.935, p < 0.001) and hamstring strength at 30° of knee flexion (right, r = 0.329, 95% CI = 0.062–0.846, p < 0.05; left, r = 0.387, 95% CI = 0.138–0.867, p < 0.05). However, the adapted test was not able to identify bilateral or hamstring to quadricep asymmetry. Test–retest reliability was high for most assessments (ICC range: 0.64–0.92), and SEM measures ranged between 5 and 12%, with the smallest change representing a change in strength ranging between 3 and 4%. In conclusion, an adapted sphygmomanometer test for hamstring and quadricep strength assessment was valid and reliable in assessing hamstring and quadricep strength but not bilateral or hamstring and quadricep asymmetry.